Continuous flow synthesis of hierarchical low silica X zeolite - Adarsh, V. K.; Shrotri, Aadesh R.; Birje, Amit R.; Nandanwar, Sachin U. (Materials Today Communications, 2024)
Zeolites, renowned for their versatile applications in catalysis, adsorption, and ion exchange, have long been synthesized using conventional batch processes. However, the inherent limitations of these methods, such as resource-intensive conditions and inconsistent product quality, underscore the need for a sustainable and efficient approach. In this study, a continuous flow synthesis process was established for the synthesis of industrially important low silica X (LSX) zeolite using a tubular reactor. The synthesis gel was subjected to aging for 5 days at room temperature to facilitate nucleation and crystal growth combined with the fast-heating rate in a tubular reactor at 363 K & 1.1 atm., which in turn produces LSX after 40 min. The synthesized product was confirmed by the XRD, FE-SEM, EDS, XRF, TEM, and N2 adsorption-desorption; the data was compared with the LSX sample synthesized by batch process. The result implies that LSX prepared by continuous flow has a pure phase of LSX with the hierarchical structure, which provides better adsorption capacity of CO2 at 298 K up to 20 bar. Due to continuous flow synthesis, the crystallization time was reduced and faster kinetics which may be helpful for scale-up the process for LSX synthesis.
Keywords: Adsorption; Carbon dioxide; continuous flow; Low silica X; Tubular reactor; zeolites